2011
DOI: 10.1007/s00198-011-1582-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of osteoporosis before and after admission to long-term care institutions

Abstract: Rates of pre-admission bisphosphonate treatment were low, but did double after LTC admission. Women were almost ten times more likely to start bisphosphonate treatment than men, although one fifth of those with documented osteoporosis were men. Although falls cause most fractures, a history of falls with injury was not associated with bisphosphonate treatment. Our findings suggest that targeting men and residents with falls for treatment with bisphosphonates might be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
8
3
Order By: Relevance
“…This could indicate that most of the fracture risk was captured by age and the medical history of prevalent fracture, which was as high as 44% (50% in women and 22% in men). This number is higher than that one found in long-term care residents in Edmonton (Canada) (34%) [29]. In this report, the patients were slightly younger (84±8 versus 86±6 years (x±SD) than in our study.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This could indicate that most of the fracture risk was captured by age and the medical history of prevalent fracture, which was as high as 44% (50% in women and 22% in men). This number is higher than that one found in long-term care residents in Edmonton (Canada) (34%) [29]. In this report, the patients were slightly younger (84±8 versus 86±6 years (x±SD) than in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…DXA-based osteoporosis diagnosis at the spine or the hip was found in 52% of the patients (58% in women and 31% in men). This figure is lower than previously reported results, which amounted to 54% to 80%, but sometimes with a diagnosis established clinically [2,11,29,[34][35][36]. Falls are particularly frequent in oldest old living in institution [37].…”
Section: Discussioncontrasting
confidence: 70%
“…Recently Rondondi et al demonstrated that in an older population of LTC residents the 10-year fracture probability appeared to be mainly determined by age and clinical risk factors obtained by medical history, rather than by BMD or the presence of vertebral fractures on radiography [30], thereby supporting the concept that prediction rules in LTC may not necessitate evaluation of BMD or imaging. Additional barriers we have identified such as lack of resources to administer fracture assessment tools, resistance from family members, costs, polypharmacy, may help explain why LTC physicians do not initiate therapies in patients at high risk for fractures including those who have recently sustained a hip fracture [14,31,32]. There have been successful multifaceted interventions in LTC that have demonstrated reduced fracture rates associated with vitamin D supplementation and anti-osteoporosis therapy use in LTC [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…1 During the aging process, morbidity associated with osteoporosis and osteoporotic fracture significantly and rapidly increases in China. 2 Fractures are a major health problem in the older population, leading to significant morbidity and mortality.…”
mentioning
confidence: 99%